The Means of Prosperity: The Neo‐Pentecostal Interpretation of the Lord's Supper in Nigeria. Issue 4 (December 2016) - Bitrus, Ibrahim
Abstract: This article investigates the Nigerian neo‐Pentecostal reinterpretation of the sacrament of the Lord's Supper using the lens of the prosperity gospel. This article describes the neo‐Pentecostal view of prosperity as an integral part of salvation, and shows how this impacts its hermeneutics of the Lord's Supper as the means of prosperity. The article argues that such neo‐Pentecostal reinterpretation does not distort the traditional significance of the Lord's Supper, but expands and complements it. As a result, Lutherans may have much to learn from the neo‐Pentecostal view of the Lord's Supper.